Characterizing and modelling the spatial patterns of wildfire ignitions in Portugal - Catry, F. X. (2008)
Catry, F. X., Rego, F. C., Moreira, F., & Bação, F. (2008). Characterizing and modelling the spatial patterns of wildfire ignitions in Portugal: Fire initiation and resulting burned area. In Modelling, Monitoring and Management of Forest Fires (Vol. 119, pp. 213-221). WITPress. https://doi.org/10.2495/FIVA080221